An Analysis of Types and Functions of Speaking Used by the Internships Students - Renata Kenanga Rinda; Nodistya Septian Indrastana; Titik Ismailia; Kaukabilla Alya Parangu; Julien Arief Wicaksono (Pioneer: Journal of Language and Literature, 2022)
This study aimed to describe the types and functions of speaking conducted by the three intership students as the hotel receptionists. To cope with the previous goal, case study was used as the research design. Additionally, observation through audio recording and interviews were implemented to collect the data. The finding of this study are: 1) one type of speaking was found which is dialogue and; 2) six functions of speaking discovered which are exchanging personal information, expressing future intentions, giving directions, giving advice & making suggestions, describing, and interacting in social situations. By practicing the type and functions above, the students were able to demonstrate the functional competence of speaking to meet their duty as hotel receptionists which is bridging good communication between the hotel and the guest. In addition, by highlighting these findings, it is expected that the data can be used by the English Study Program to prepare the material for the speaking course before succeeding students complete the internship program as hotel receptionists.